Exponential decay of transient values in positive nonlinear systems - Kaczorek, Tadeusz (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
The exponential decay of transient values in nonlinear continuous-time standard and fractional orders with linear dynamical positive feedback systems and of positive linear parts is investigated. Sufficient conditions for the exponential decay of transient values in this class of positive nonlinear systems are established. Procedures for the computation of gains characterizing the class of nonlinear elements are given and illustrated in simple examples.